SCGB3A1‐Epi and KLK10‐Epi Crosstalk With Fibroblasts Promotes Liver Metastasis of Breast Cancer and Pancreatic Ductal Adenocarcinoma - Zixue Xuan; Zhongxiu Wu; Lei Cheng; Jinying Jiang; Yuan Zhang; Yuxuan Xia (Cancer Medicine, 2025)
ABSTRACT Background The liver often serves as the principal site for metastatic spread from a variety of solid tumors, and metastasis to the liver markedly diminishes patient survival. Single‐cell RNA sequencing (scRNA‐seq) has helped uncover the complexity of liver tumor metastasis. However, the key cellular subtypes of breast cancer and pancreatic ductal adenocarcinoma (PDAC) with liver metastasis and their mechanisms of action are unclear, making treatment difficult. Methods We used integrated scRNA‐seq data to dissect liver metastasis‐specific epithelial cell subtypes in breast cancer and PDAC, and elucidated their mechanisms through functional analyses and intercellular interactions with fibroblasts. Results Interestingly, our results show that SCGB3A1‐Epi and KLK10‐Epi are key drivers of liver metastasis in breast cancer and PDAC, respectively. These subtypes are associated with high malignancy rates and involved in oxidative phosphorylation and other critical pathways. Specific ligand‐receptor interactions were observed between these epithelial subtypes and fibroblasts, with significant interactions between CD74‐APP receptors in SCGB3A1‐Epi and Fib‐11 in breast cancer and between SPP1‐CD44 receptors in KLK10‐Epi and Fib‐11 in PDAC. High expression levels of Fib‐11 and CD74 were correlated with improved survival in breast cancer, whereas high SPP1 and CD44 expression predicted worse PDAC outcomes. Fib‐11 is implicated in signaling pathways associated with tumor metastasis, particularly those involving cell adhesion molecules. Conclusions We revealed the cellular heterogeneity of liver metastasis and provided a crucial research foundation for developing novel therapeutic strategies to specifically target metastatic cell subtypes, thereby enhancing patient prognosis.